Unknown diabetes: a case report - Cirla, Piero Emanuele; Martinotti, Irene (La Medicina del Lavoro, 2020)
Introduction: Diabetes is often diagnosed in people who already show clear signs and symptoms of complications. This leads to a significant impact both on general health costs and quality of life (private and working). Corporate social responsibility actions could play a significant role managing and supporting physical, mental and social well-being of the worker affected by diabetes. Objectives: To report a case of management of unknown diabetes. Results: Type 2 Diabetes in an office worker (health risks: VDU, organization and stress, use of company car), with sudden visual impairment, detected during a health surveillance periodical consult. The diagnosis was “diabetes mellitus with proliferative retinopathy, macular edema and predominantly sensitive polyneuropathy”. Discussion: The most important impairment concerned the distance visual acuity, with the consequent impossibility to drive a car. The worker continued to work in the same advanced tertiary sector company adapting to the new condition of susceptibility (transition from customer directed operations to manager of working groups, limited VDU use, and no company car use). The depressive implications, caused by the impacts in lifestyle, have been effectively counterbalanced by the strong social support received from the work organization and colleagues. Conclusions: A constructive reaction of the “company system” is able to provide an useful and effective support to manage diabetes and work, with tangible positive implications on overall health status.